If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 4a = 55 Reorder the terms: 4a + b = 55 Solving 4a + b = 55 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 4a + b + -1b = 55 + -1b Combine like terms: b + -1b = 0 4a + 0 = 55 + -1b 4a = 55 + -1b Divide each side by '4'. a = 13.75 + -0.25b Simplifying a = 13.75 + -0.25b
| x^3+7x-4x-28=0 | | lnx-ln(x+5)=0 | | 1/5w-3 | | 2x-2-2x-6=0 | | 4p+5a=37 | | 60/(200x5) | | 9y+9y=18y | | 3n-8=5 | | 0.50x+0.75y=20+-11.50x | | 2x^3+28x^2+96=0 | | 5/3s=443/5 | | 45.9=(2x^2)/(3-x)^2 | | 2=12/r | | 2x^2+z-3=0 | | 12/n=9/13 | | -4(3-x)-(-3-5x)=2(-x-3x-1) | | 5x-x-8=9x | | 3x+2y-z=-10 | | 18+10m=4+8m | | -10(s+4)=-14 | | 0.63n=328 | | 0=-16t^2+46t-6 | | 11+3x=15-3x-18x^2 | | -4(3-x)-(-3-5x)=(x-3x-1) | | (7r-24)=9 | | 11+3x=15-3x-18x^2 | | -4(3-x)-(-3-5x)=(x-3x-1) | | 3f-8=2(f-4) | | 3f-8=2(f-4) | | -3=5-4y | | -3=5-4y | | -3=5-4y |